LEGAL PROTECTION OF CHILDREN AN WOMAN FROM DOMESTIC VIOLENCE (RESEARCH METHODS BY THE NORTH SUMATERA KPAI) - Joel F. Toldo Sumihar Sitohang; Mhd. Azhali Siregar; Lidya Rahmadhani (PT. Radja Intercontinental Publishing, 2026)
Domestic violence (KDRT) is a form of human rights violation that has serious impacts, especially on women and children. This article aims to analyze the form of legal protection provided to women and children victims of domestic violence in Indonesia. The results of the analysis show that although there are regulations such as Law Number 23 of 2004 concerning the Elimination of Domestic Violence, as well as the Child Protection Law, there are still various challenges in its implementation, such as patriarchal culture, low legal awareness of the community, and weak law enforcement. Further efforts are needed in the form of education, training of law enforcement officers, and empowerment of victims so that legal protection can run optimally.